THE IMPACT OF LEADERSHIP BEHAVIOR ON SCHOOL PERFORMANCE - Hidayat, Nandang; Wulandari, Farida (Jurnal Cakrawala Pendidikan, 2020)
Abstract: Principal leadership is an important component that determines the direction and achievement of school performance. The purpose of this study was to identify the behavior and formulate a theoretical model of the Structural Equation Model (SEM) dimension of the principal leadership on school performance. This study used a qualitative approach using the phenomenological method. Participants in this study were 8 principals and 16 teachers from 8 private junior high schools in the Bogor City and Regency. Data collection employed in-depth interview techniques, observation of work behavior, and document review. Data validity was based on credibility, transferability, dependability and confirmability criteria during the data collection. Data analysis was carried out through the stages of organizing data, sorting them into manageable units, searching and finding patterns, synthesizing, and drawing conclusions. This research finds the following: 1) the leadership behavior of private secondary school principals to achieve optimal school performance tends to be situational and conditional; 2) interrelation in the form of direct or indirect causal relationships between the principal leadership behavior and the school performance can be formulated in the form of the theoretical SEM consisting of a four-level dimension of the principal leadership.